The final martyrs - Endō, Shūsaku 1923-1996 (New Directions Publ. Co., 1994)
Eleven stories by a cosmopolitan Japanese writer. The title story is on the persecution of Christians in Japan; Japanese in Warsaw is on pimping for tourists; Adieu, set in France, is on old age; and Shadows is a young man's cry from the heart when his role model, a Spanish priest, abandons the church for a woman. By the author of The Golden Country.
Keywords: Endō, Shūsaku <1923-1996> -- Translations into English; Endō, Shūsaku -- 1923-1996